2015
DOI: 10.1016/j.ajpath.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Human Polyomavirus Receptor Distribution in Brain Parenchyma Contrasts with Receptor Distribution in Kidney and Choroid Plexus

Abstract: The human polyomavirus, JCPyV, is the causative agent of progressive multifocal leukoencephalopathy, a rare demyelinating disease that occurs in the setting of prolonged immunosuppression. After initial asymptomatic infection, the virus establishes lifelong persistence in the kidney and possibly other extraneural sites. In rare instances, the virus traffics to the central nervous system, where oligodendrocytes, astrocytes, and glial precursors are susceptible to lytic infection, resulting in progressive multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 97 publications
6
49
0
Order By: Relevance
“…Wild-type JCV strains are also able to make facultative use of the GAG-dependent entry pathway, allowing them to remain partially infectious when either GAG or sialic acid engagement is blocked. The existence of this previously unknown sialylated glycan-independent infectious entry pathway could help explain why JCV can robustly infect human astrocytes and oligodendrocytes in vivo (Kondo et al, 2014), despite the fact that these cell types appear to lack previously identified sialylated glycan receptors for the virus (Haley et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Wild-type JCV strains are also able to make facultative use of the GAG-dependent entry pathway, allowing them to remain partially infectious when either GAG or sialic acid engagement is blocked. The existence of this previously unknown sialylated glycan-independent infectious entry pathway could help explain why JCV can robustly infect human astrocytes and oligodendrocytes in vivo (Kondo et al, 2014), despite the fact that these cell types appear to lack previously identified sialylated glycan receptors for the virus (Haley et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that JCPyV binding to and infection of cells in the brain including, astrocytes, oligodendrocytes, and neurons, is sialic-acid-independent in an in vivo infection. Haley et al demonstrated that astrocytes and oligodendrocytes from human brain tissues were negative for LSTc [81]. Therefore, viruses isolated from PML patients with mutations in VP1 within the sialic acid binding sites could possibly lead to neuroinvasion via a sialic acid-independent manner through interactions with an alternate receptor or through a receptor-independent invasion mechanism that has been demonstrated for other viruses [82, 83].…”
Section: Pml-associated Vp1 Mutationsmentioning
confidence: 99%
“…Interestingly, 5-HT 2 Rs are expressed on a variety of cells in the CNS, including astrocytes and oligodendrocytes, and in the kidney, including the distal tubules and collecting ducts, all of which are sites of JCPyV infection [81, 88, 89]. Furthermore, 5-HT 2 Rs are expressed on neurons, and subtype 2A is found abundantly in the cerebral cortex [90] where JCPyV has been identified in sites of significant demyelination in individuals with PML [41, 43].…”
Section: Serotonin Receptors In Jcpyv Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…5 The resulting Neu5Acα2–6LNnT (LSTc) represents a common structure found in human milk 11 and on mammalian cell surface. 53 …”
Section: Introductionmentioning
confidence: 99%